2017
DOI: 10.15421/nvlvet7521
|View full text |Cite
|
Sign up to set email alerts
|

Екстракт Журавлини В Технології Варених Ковбас З М’ясом Водоплавної Птиці

Abstract: Стаття присвячена дослідженню ефективності використання екстракту журавлини в технології м’ясомістких варених ковбас із м’ясом качки Пекінської та м’ясом індика механічного обвалювання. На сьогоднішньому етапі розвитку м’ясопереробної промисловості актуальним є питання пошуку альтернативних синтетичним, ефективних препаратів природного походження, що здатні уповільнювати окисні процеси і мають високу антиоксидантну активність. М’ясо водоплавної птиці є перспективною сировиною для м’ясної промисловості, але вон… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some studies [24,25] are devoted to the efficiency of using imported extracts of medicinal and spice-aromatic plants such as salvia, rosemary, ginger, and green tea. As a result of studying the antioxidant properties of the plant extracts, it was found that the highest content of total fat-soluble and water-soluble antioxidants is in the extracts of rosemary and green tea.…”
Section: Analysis Of the Influence Of Rosemary And Grape Seed Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [24,25] are devoted to the efficiency of using imported extracts of medicinal and spice-aromatic plants such as salvia, rosemary, ginger, and green tea. As a result of studying the antioxidant properties of the plant extracts, it was found that the highest content of total fat-soluble and water-soluble antioxidants is in the extracts of rosemary and green tea.…”
Section: Analysis Of the Influence Of Rosemary And Grape Seed Extractmentioning
confidence: 99%
“…As a result of studying the antioxidant properties of the plant extracts, it was found that the highest content of total fat-soluble and water-soluble antioxidants is in the extracts of rosemary and green tea. It has been shown that using rosemary and green tea extracts to stabilize the lipids of minced semi-finished meat products can reduce the rate of forming products of hydrolysis, as well as primary and secondary oxidation of lipids [25].…”
Section: Analysis Of the Influence Of Rosemary And Grape Seed Extractmentioning
confidence: 99%